# Yahoo Web Search

1. ### Prove that LHS =RHS:(1/sec^2A-cos^2A+1/cosec^2A-sin^2A)sin^2Acos^2A=1-sin^2Acos^2A/2+sin^2Acos^2A?

...^2A/2+sin^2Acos^2A let us take the LHS first (1/sec^2A-cos^2A+1/cosec^2A-sin^2A)sin...

2 Answers · Science & Mathematics · 23/05/2008

2. ### Fx + Fy = Z I need to group the F variables alone on the LHS ?

U can take F outside the LHS by F(x+y)= Z then cross multiply F = Z / (x+y...

1 Answers · Science & Mathematics · 25/11/2009

3. ### Prove that cosecA+cotA=1/(cosecA-cotA) using the LHS of the identity?

you have { LHS } 1 / sin A + cos A / sin A = [ 1+ cos A] / sin A = sin² A / { sin A [ 1 - cos A ] }= sin A / [ 1 - cos A ] = 1 / [ 1/sin A - cos A / sin A] =result

3 Answers · Science & Mathematics · 22/09/2011

4. ### in maths RHS=LHSwhile in ms excel dont have LHS explain with mathematical refernce?

...you could just as well say that the value displayed in the cell is the LHS . On the other hand, if you want to enter a formula for an equation into a cell...

2 Answers · Science & Mathematics · 18/10/2012

5. ### How does LHS equal RHS?

Let...[1 / 2*square root of X] = K LHS = K / (X-2)....multiply top and bottom by -1 ...= -K / -(X -2) = -K / (2 -X ) = RHS

2 Answers · Science & Mathematics · 25/11/2011

6. ### Show LHS = RHS for this sum (to n--> infinity)?

...in line 2 above, and then show that C=0. Let x→0.Then the LHS →0 and the RHS→ln1 (since x/sinx→1) =0. Thus C=0]. ...

1 Answers · Science & Mathematics · 02/08/2012

7. ### In maths, what does LHS and RHS stand for?

... about. As in: √(x - 1) + 1/√(x - 1) = 0 I might say, the LHS simplifies to: x/√(x - 1) Then I might say, so now we...

1 Answers · Science & Mathematics · 09/03/2010

8. ### Verifying Trig Identities: cot (-t) + tan (-t)/cot t = tan t LHS to RHS please!?

This is not an identity. The LHS does not equal the RHS. Try putting t = pi/4 in the LHS , and it will not equate with the RHS.

1 Answers · Science & Mathematics · 13/04/2010

9. ### what does LHS mean in math?

Left Hand Side e.g x + 1 >= 7 x + 1 is the LHS P.S: Allen is right

4 Answers · Science & Mathematics · 11/11/2010

10. ### {(1/sinx) - (1/tanx)}^2 = (1-cosx)/(1+cosx). Prove LHS = RHS. Help anyone?

...cos ^2 x) = (1- cos x)^2/((1-cos x)(1+ cos x)) = (1- cos x)/(1+ cos x) edit: for LHS to be defined sin x cannot be zero( if it is zero ...

7 Answers · Science & Mathematics · 12/04/2012